Comunicação e Ciência da informação: corresponsabilidades em torno da decolonialidade informacional - Souza, Franceline Patricia de (Universidade Federal de São Carlos, 2022)
It was found as a research problem to be investigated the need to understand, in a more systematic way, how studies on decoloniality are being presented and developed in the context of Communication, as an area of knowledge. More specifically, we tried to identify how much research in Communication is considering the issues that involve the claims of decoloniality in the development of their practices. From this place of Communication, the aim was to develop approaches to Information Science studies, which concern the studies that the area develops in Marketing aimed at information products and services. The transversal objective that was intended to be reached was to identify elements that allowed to discuss how elements of decolonization of advertising, developed in the scope of Communication, could be considered by Information Science, when developing actions and Marketing of its informational products and services. Thus, in an interdisciplinary perspective, the objective was to present, as an result of research, a set of reflections, with a communicative and decolonial basis, for informational studies and practices, especially those that concern informational marketing actions. For this, the method used was composed of a set of exploratory actions, which were supported by bibliographic and documentary research. And the argumentative construction of the research was based on a narrative review of the literature, since it was not their objective to present an art state on the subjects discussed, but yes, to list studies that would make possible an argumentative and propositional construction to the field of Information Science, based on Communication.
Communication and Information Science: co-responsibilities around informational decoloniality
Keywords: Comunicação; Ciência da Informação; Decolonialidade; Marketing; Communication; Information Science; Decolonization; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO